2020
DOI: 10.3892/ol.2020.11925
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects and the mechanism underlying 2‑methoxyestradiol in human osteosarcoma <em>in&nbsp;vitro</em> and <em>in&nbsp;vivo</em>

Abstract: Osteosarcoma (OS) occurs in both children and adolescents and leads to a poor prognosis. 2-methoxyestradiol (2-ME) has a strong antitumor effect and is effective against numerous types of tumor. However, 2-ME has a low level of antitumor effects in OS. The present study investigated the effects of 2-ME on the proliferation and apoptosis of human MG63 OS cells. The potential biological mechanisms by which 2-ME exerts its biological effects were also investigated in the present study. The results of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…A previous study showed that at least 10 μM of 2ME was required to increase caspase-3 and the increase was gradual as well. This demonstrates that the intrinsic-mediated caspase-3 activation pathway is involved in 2ME mediated apoptosis (Tang et al., 2020 ). We reported that 2ME-INVA-APA downregulated the expression of both TNF-α and NF-κB.…”
Section: Discussionmentioning
confidence: 88%
“…A previous study showed that at least 10 μM of 2ME was required to increase caspase-3 and the increase was gradual as well. This demonstrates that the intrinsic-mediated caspase-3 activation pathway is involved in 2ME mediated apoptosis (Tang et al., 2020 ). We reported that 2ME-INVA-APA downregulated the expression of both TNF-α and NF-κB.…”
Section: Discussionmentioning
confidence: 88%
“…Numerous studies in BC, both in vitro and in vivo. have demonstrated that 2‐ME has anti‐angiogenic and anti‐proliferative properties 14–21 . Moreover, the use of 2‐ME has been shown to enhance the effects of chemotherapy in the treatment of BC 22 .…”
Section: Introductionmentioning
confidence: 99%
“…have demonstrated that 2‐ME has anti‐angiogenic and anti‐proliferative properties. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Moreover, the use of 2‐ME has been shown to enhance the effects of chemotherapy in the treatment of BC. 22 For example, combining 2‐ME with paclitaxel, a widely used chemotherapy drug, has been shown to improve treatment outcomes in preclinical models of BC.…”
Section: Introductionmentioning
confidence: 99%